Preventing Thin Film Dewetting via Graphene Capping. Issue 36 (19th July 2017) - Cao, Peigen; Bai, Peter; Omrani, Arash A.; Xiao, Yihan; Meaker, Kacey L.; Tsai, Hsin‐Zon; Yan, Aiming; Jung, Han Sae; Khajeh, Ramin; Rodgers, Griffin F.; Kim, Youngkyou; Aikawa, Andrew S.; et al.
Abstract : A monolayer 2D capping layer with high Young's modulus is shown to be able to effectively suppress the dewetting of underlying thin films of small organic semiconductor molecule, polymer, and polycrystalline metal, respectively. To verify the universality of this capping layer approach, the dewetting experiments are performed for single‐layer graphene transferred onto polystyrene (PS), semiconducting thienoazacoronene (EH‐TAC), gold, and also MoS2 on PS. Thermodynamic modeling indicates that the exceptionally high Young's modulus and surface conformity of 2D capping layers such as graphene and MoS2 substantially suppress surface fluctuations and thus dewetting. As long as the uncovered area is smaller than the fluctuation wavelength of the thin film in a dewetting process via spinodal decomposition, the dewetting should be suppressed. The 2D monolayer‐capping approach opens up exciting new possibilities to enhance the thermal stability and expands the processing parameters for thin film materials without significantly altering their physical properties. Abstract : A monolayer 2D capping layer is shown to be able to effectively suppress the dewetting of thin films of both polymer and polycrystalline metal. Thermodynamic modeling indicates that the exceptionally high Young's modulus and surface conformity of 2D capping layers such as graphene and MoS2 substantially suppress surface fluctuations and thus dewetting.